More than a warning: Expanding the role of communication in Eastern Caribbean volcano science - Graham, Omari; Edwards, Stacey; Robertson, Richard (Frontiers in Earth Science, 2022)
The Education and Outreach (E&O) team at The University of the West Indies Seismic Research Centre (UWI-SRC) manages all the agency’s external communications. The team also works to raise public awareness of geological hazards in the UWI-SRC’s Eastern Caribbean region of responsibility. Within the Caribbean region, most communication research related to disaster risk up until now has focused on communication during crises. Using semi-structured interviews and document review we investigated the impact of strategic communication in a long-term, multi-hazard monitoring programme. A qualitative analysis highlighted the equal importance of crisis communication during unrest and outreach work during quiescent periods. The UWI-SRC’s communication programme has been effective in: (1) maintaining multidirectional communication pathways between scientists, civil authorities and the public (2) broadening the Centre’s operational footprint (3) building regional scientific capacity and (4) strengthening organisational credibility. This article examines the contribution of specialist communication throughout the disaster management cycle, particularly in managing volcanic risk in the English-speaking Eastern Caribbean. It argues that significant societal value can be added to the scientific work engaged in by advisory scientists by embracing a multi-level communication strategy.